Age of the magnetically active WW Psa and TX Psa members of the β Pictoris association - Messina, S. (2017)
There are a variety of different techniques available to estimate the ages of pre-main-sequence stars. Components of physical pairs, thanks to their strict coevality and the mass difference, such as the binary system analyzed in this paper, are best suited to test the effectiveness of these different techniques. We consider the system WW Psa + TX Psa whose membership of the 25-Myr β Pictoris association has been well established by earlier works. We aim to investigate which age-dating technique provides the best agreement between the age of the system and that of the association. Methods. We have photometrically monitored WW Psa and TX Psa and measured their rotation periods as P = 2.37 d and P = 1.086 d, respectively. We have retrieved their Li equivalent widths from the literature and measured their effective temperatures and luminosities. We investigated whether the ages of these stars derived using three independent techniques, that is based on rotation, Li equivalent widths, and the position in the HR diagram are consistent with the age of the β Pictoris association. We find that the rotation periods and the Li contents of both stars are consistent with the distribution of other bona fide members of the cluster. On the contrary, the isochronal fitting provides similar ages for both stars, but a factor of about four younger than the quoted age of the association, or about 30% younger when the effects of magnetic fields are included. Conclusions. We explore the origin of the discrepant age inferred from isochronal fitting, including the possibilities that either the two components may be unresolved binaries or that the basic stellar parameters of both components are altered by enhanced magnetic activity. The latter is found to be the more reasonable cause, suggesting that age estimates based on Li content are more reliable than isochronal fitting for pre-main-sequence stars with pronounced magnetic activity.